Pengaruh Kapabilitas Organisasi Terhadap Kinerja Bisnis (Studi Pada PT. Sanjaya Rezeki Mas Karawang) - Hendra Susila; Dede Jajang Suyaman; Sonny Hersona GW (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to analyze the influence of organizational capabilities on the business performance of PT Senjaya Rejeki Mas Karawang. The method used in this research is descriptive and verification analysis with a quantitative approach. The sampling technique used in this research is simple random sampling. The number of samples used were 114 respondents. The data analysis technique used is a simple regression analysis technique with the help of the SPSS version 18 application. The results of this study indicate that the organizational capabilities and business performance of PT Senjaya Rejeki Mas Karawang are currently good. And verifiably the results of this study show that organizational capability has a positive and significant effect on the business performance of PT Senjaya Rejeki Mas Karawang by 73.5%. While the remaining 26.5% comes from other factors not examined. Keywords: organizational capability, business performance